Faktor-Faktor Penggerak Tax Avoidance pada Perusahaan Basic Material di BEI : Transfer Pricing, Capital Intencity dan Koneksi Politik Dimana Firm Size sebagai Variabel Pemoderasi - Moh. Yuddy Yudawirawan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Tax avoidance remains a critical issue in corporate financial management, particularly in emerging markets where regulatory enforcement varies. This study investigates the effect of transfer pricing, capital intensity, and political connections on tax avoidance, with firm size as a moderating variable. The research uses a quantitative approach, focusing on companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Out of 108 companies, 12 met the purposive sampling criteria, yielding 60 financial report data points. Data were analyzed using panel data regression with the assistance of EViews 13 software. The analysis included descriptive statistics, classical assumption tests, panel regression model selection tests, and hypothesis testing. The F-test results indicate that transfer pricing, capital intensity, and political connections collectively have a significant influence on tax avoidance. However, the t-test results reveal that only capital intensity and political connections have a significant individual effect on tax avoidance, while transfer pricing does not. Furthermore, the Moderated Regression Analysis (MRA) shows that firm size moderates the relationship between capital intensity and tax avoidance but does not moderate the effect of transfer pricing or political connections on tax avoidance.